Evaluation of the ASTERTM process in the presence of suspended solids. (15th May 2015) - van Zyl, Andries W.; Huddy, Robert; Harrison, Susan T.L.; van Hille, Robert P.
Graphical abstract: Highlights: ASTER TM process successfully implemented in the presence of 5.5% (m/v) suspended solids. Thiocyanate degradation efficiency negatively affected by pH < 6. Suspended solids prevented floc or biofilm formation. Microbial diversity significantly lower than in similar system with no solids. Abstract: The ability to recycle and reuse process water is a major contributing factor toward increased sustainability in the mining industry. However, the presence of toxic compounds has prevented this in most bioleaching operations. The ASTER TM process has been used for the bioremediation of cyanide (CN) and thiocyanate (SCN − ) containing effluents at demonstration and commercial scale, increasing the potential for recycling of the treated effluent. The process relies on a complex consortium of microorganisms and laboratory tests have shown that the biomass retention, in suspended flocs or attached biofilm, significantly improved SCN − degradation rates. The current research evaluated the process performance in the presence of suspended solids (up to 5.5% m/v) ahead of implementation at a site where complete tailings removal is not possible. Experiments were performed in four 1 l CSTRs (with three primary reactors in parallel at an 8 h residence time, feeding one secondary reactor at a 2.7 h residence time). Stable operation at the design specifications (5.5% solids, 100 mg/l SCN − feed, effluent SCN − <1 mg/l) was achieved within 50 days, including a period of adaptation. The pH had the most significant effect on performance, with significant inhibition below pH 6. The presence of gypsum and anhydrite phases in the fresh tailings was most likely responsible for the observed decrease in pH. A maximum SCN − degradation rate of >57 mg/l/h was achieved, despite no obvious floc formation. Microbial ecology studies (16S rRNA clone library) revealed reduced diversity relative to reactors operated without suspended solids.